Design and construction of a pilot plant for the continuous biodisel production (2008)
This work develops a pilot system for biodiesel production and its future implementation at regional or national level. In this research, the most important parameters in the production and quality of biodiesel were determined preliminarily and they turned out to be the alcohol-oil molar relation and the necessary amount of catalyst. Once these values were obtained, the pilot plant was built and greater scale production and quality test took place. These tests produced satisfactory results concerning power, torque, consumption and polluting emissions, and are very related to the results that have been obtained in other works with biodiesel at national and international level.